2015
DOI: 10.1259/dmfr.20140325
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of benign and malignant lesions of the tongue by using diffusion-weighted MRI at 3.0 T

Abstract: Objectives: Diffusion-weighted MRI (DWI) has been introduced in head and neck lesions and adds important information to the findings obtained through conventional MRI. The purpose of this study was to assess the role of DWI in differentiating benign and malignant lesions of the tongue at 3.0-T field strength imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…These observations were similar to those from our previous study on early laryngeal carcinoma ( 12 ) and to those of other previous studies on head and neck carcinomas ( 4 , 10 , 15 ). Li et al ( 15 ) revealed that the mean ADC value of malignant lesions of the tongue [(1.08±0.16)×10 −3 mm 2 /sec] was lower than that of benign lesions [(1.68±0.33)×10 −3 mm 2 /sec] and cystic lesions [(2.21±0.35)×10 −3 mm 2 /sec; P<0.001]. ROC analysis revealed that the AUC was 0.963 and the optimal threshold for the ADC cut-off point was 1.31×10 −3 mm 2 /sec for predicting malignancy ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations were similar to those from our previous study on early laryngeal carcinoma ( 12 ) and to those of other previous studies on head and neck carcinomas ( 4 , 10 , 15 ). Li et al ( 15 ) revealed that the mean ADC value of malignant lesions of the tongue [(1.08±0.16)×10 −3 mm 2 /sec] was lower than that of benign lesions [(1.68±0.33)×10 −3 mm 2 /sec] and cystic lesions [(2.21±0.35)×10 −3 mm 2 /sec; P<0.001]. ROC analysis revealed that the AUC was 0.963 and the optimal threshold for the ADC cut-off point was 1.31×10 −3 mm 2 /sec for predicting malignancy ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Li et al ( 15 ) revealed that the mean ADC value of malignant lesions of the tongue [(1.08±0.16)×10 −3 mm 2 /sec] was lower than that of benign lesions [(1.68±0.33)×10 −3 mm 2 /sec] and cystic lesions [(2.21±0.35)×10 −3 mm 2 /sec; P<0.001]. ROC analysis revealed that the AUC was 0.963 and the optimal threshold for the ADC cut-off point was 1.31×10 −3 mm 2 /sec for predicting malignancy ( 15 ). A meta-analysis investigating DWI as a tool for differentiating malignancy from benign thyroid nodules undertaken by Wu et al ( 9 ) revealed that DWI sensitivity was 0.91 (95% CI, 0.86–0.94), specificity was 0.92 (95% CI, 0.84–0.97), and ROC curves demonstrated that AUC was 0.94 (95% CI, 0.92–0.96), indicating a high level of overall accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why malignant tumours have lower ADC values are not well understood but is probably related to a combination of higher cellularity, tissue disorganization and increased extracellular space tortuosity, all contributing to reduced motion of water. 8 Although with different b-values and different optimal ADC thresholds, most previous studies inevitably proved the ability of DWI in differentiating malignant from benign head and neck tumours, [15][16][17][18][19][20][21][22][23][24] except that diagnostic dilemma exists in cholesteatoma, salivary gland tumours and lymph nodes. 8,25 However, the comparison of diagnostic ability between DWI and conventional MRI was less performed.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Furthermore, some reports showed the application of DWI with calculation of apparent diffusion coefficient (ADC) in the differentiation between malignant and benign diseases in head and neck. [6][7][8][9][10] Studies regarding absolute ADC values in the normal human brain and the effect of aging on diffusion are scarce, and only a few reports involving small numbers of subjects have been published. [11] Moreover, age is an important factor for spinal cord injury and repair.…”
Section: Introductionmentioning
confidence: 99%